Physiologic Specialization of Puccinia triticina on Wheat in the United States in 2009 - Kolmer, J A (Plant disease, 2011)
Collections of Puccinia triticina were obtained from rust-infected leaves provided by cooperators throughout the United States and from surveys of wheat (Triticum aestivum) fields and wheat breeding plots by United States Department of Agriculture-Agricultural Research Service personnel in the Great Plains, Ohio River Valley, southeast, California, and Washington State in order to determine the virulence of the wheat leaf rust population in 2009. Single uredinial isolates (591 in total) were derived from the collections and tested for virulence phenotype on lines of Thatcher wheat that are near-isogenic for leaf rust resistance genes Lr1, Lr2a, Lr2c, Lr3a, Lr9, Lr16, Lr24, Lr26, Lr3ka, Lr11, Lr17a, Lr30, LrB, Lr10, Lr14a, Lr18, Lr21, and Lr28 and a winter wheat line with Lr39/41. Forty-one virulence phenotypes were described. Virulence phenotypes MLDSD, TCRKG, and TDBGG were the three most common phenotypes. Phenotype MLDSD is virulent to Lr17 and Lr39/Lr41 and was widely distributed throughout the United States. Phenotype TCRKG is virulent to Lr11, Lr18, and Lr26 and is found mostly in the soft red winter wheat region in the eastern United States. TDBGG is virulent to Lr24 and was found in both the soft red winter wheat and hard red winter wheat regions. Virulence to Lr21 was not found in any of the tested isolates. Virulence to Lr11, Lr18, and Lr26 increased in 2009 in the soft red winter wheat regions. Virulence to Lr17 and Lr39/Lr41 increased in the Great Plains region. Two separate epidemiological zones of P. triticina in the soft red winter wheat region of the southern and eastern states and in the hard red wheat region of the Great Plains were described